ANALISA PERBANDINGAN BIAYA DAN WAKTU PERKERASAN KAKU METODE CAST IN SITU (CIS) DAN METODE PRECAST PRESTRESSED CONCRETE PAVEMENT (PPCP) (Studi Kasus Pada Proyek Jalan Tol X Di Jawa Timur) - Rakmat Dwi Anugrah Putra, Sugiharti (Prokons: Jurnal Teknik Sipil, 2014)
Concrete cracks on pavement occurred at X Toll Road implementation before the pavement attained the expected time. Consquently, it must be removed and it caused cost and time loss. CIS is a method in which fresh concrete is cured in site, and PPCP is the one in which the pavement is stressed by stretching the steel tendon and anchor into the fresh concrete before live load is applied.  The objective of the study is to compare method between the two from cost and time. California Bearing Ratio (CBR), technical drawing, daily passing vehicle rate, concrete, and itemized work cost were employed. National Association of Australian State Road Authorities (NAASRA) was employed to implement the rigid pavement; American Concrete Institute (ACI) was based on PPCP for the pavement depth design.The calculations result in 27 cm deep of CIS and 20 cm deep of PPCP; IDR 216.336.692.351,25   and 208 workday for CIS ; IDR 222.068.995.407,73 and 158 workdays for PPCPKeywords: cast in situ, cost and time, rigid pavement, prestressed precast concrete pavement